Interactive Multimedia Based on Adobe Flash Software on Thematic Learning for Grade V Elementary School - Salwa Annisa Hasri; Yanti Fitria; Yeni Erita (Indonesian Journal Of Educational Research and Review, 2023)
Nowadays the teachers have not utilized the use of IT-based media in the learning process, so students feel less motivated in the learning process and make students less understand the material delivered by the teacher. This research aims to develop learning multimedia based on Adobe Flash software that is valid, practical and effective for improve student learning outcomes. The subjects of this study consisted of media experts, material experts, linguists, teachers and fifth grade students at several schools. This type of research is Research and Development (research and development). This research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data obtained will be analyze using descriptive percentages and qualitative data. Data collection in the study used a scale 5 questionnaire to determine the level of validity, practicality, and student learning motivation as well as to determine student learning outcomes by means of pretest and post-test using objective questions. The results showed that the development of multimedia learning using Adobe Flash software was declared valid for use in class V elementary school. Learning multimedia based on Adobe Flash software is also effective in improving student learning outcomes. This can be seen from the results of the pretest and post-test comparisons. Thus, learning multimedia using Adobe Flash is valid, practical and effective and suitable for use in the learning process in class V of elementary school.